The Relationship between Tourism and Economic Growth: Evidence from Oceania - Nguyen, Anh Tru (Journal of Tourism Management Research, 2020)
The article aims to examine the relationship between tourism and economic growth in four Oceanian countries between 1998 and 2017 using a VAR model. Results showed that international tourism receipts have a positive relationship with international tourism arrivals. Further, international tourism arrivals positively affect GDP growth rate, but international tourism receipts have a negative influence on GDP growth rate. These imply that economic growth of four Oceanian countries depends on the quantity of international tourists rather than expenditures of international visitors in domestic markets. In the short run, there is a directional relationship running from international tourism arrivals to international tourism receipts; from GDP growth rate to tourism arrivals; and from GDP growth rate to tourism receipts. In the long run, there is a relationship among variables at the 1% critical value and the 5% critical value. Lastly, we recommend that the tourism sector in the region should be improved to exploit expenditures of international tourists.